Foreign Trade in Special Economic Zones in Poland - Jarosław M. Nazarczuk; Stanisław Umiński (UWM, 2019)
The book covers unique approach to the analysis of foreign trade. It presents a macroeconomic, mesoeconomic and microeconomic perspective on the effects of special economic zones operation with regard to foreign trade to provide a better understanding of consequences of SEZs' establishment (for country, region or a firm). To the knowledge of the authors, this is the first (so comprehensive) evaluation of SEZs functioning thereof. The monograph summarizes a significant part of the results of the research project entitled “Foreign Trade in Special Economic Zones in Poland”, financed by the National Science Centre in Poland (project no. DEC-2013/11/D/HS4/04007). The project aimed at identifying the real impact of SEZs on Poland's trade turnover. Its implementation focused on expanding the available scope of knowledge on the impact of the SEZs on the Poland's trade and has enabled to join in the ongoing national and international academic debate on further functioning of various types of areas of special preference. Moreover, the research permitted for identification of microeconomic determinants of the impact of the SEZs on business entities in terms of their export activities contributing to a widening of scientific achievements in the field of economics.
Keywords: F14; H25; H32; R3; 330; special economic zone; SEZ; foreign trade; impact evaluation; privileged areas; tax exemptions; regional trade; FDI